Catalytic technologies for CO hydrogenation for the production of light hydrocarbons and middle distillates - Chae, Ho Jin; Kim, Jin Ho; Lee, Soo Chool; Kim, Hyo Sik; Jo, Seong Bin; Ryu, Jae Hong; Kim, Tae Young; Lee, Chul Ho; Kim, Se Jeong; Kang, Suk Hwan; Kim, Jae Chang; Park, Myung June (Catalysts, 2020)
In South Korea, where there are no resources such as natural gas or crude oil, research on alternative fuels has been actively conducted since the 1990s. The research on synthetic oil is subdivided into Coal to Liquid (CTL), Gas to Liquid (GTL), Biomass to Liquid (BTL), etc., and was developed with the focus on catalysts, their preparation, reactor types, and operation technologies according to the product to be obtained. In Fischer–Tropsch synthesis for synthetic oil from syngas, stability, CO conversion rate, and product selectivity of catalysts depends on the design of their components, such as their active material, promoter, and support. Most of the developed catalysts were Fe-and Co-based catalysts and were developed in spherical and cylindrical shapes according to the reactor type. Recently, hybrid catalysts in combination with cracking catalysts were developed to control the distribution of the product. In this review, we survey recent studies related to the design of catalysts for production of light hydrocarbons and middle distillates, including hybrid catalysts, encapsulated core–shell catalysts, catalysts with active materials with well-organized sizes and shapes, and catalysts with shape-and size-controlled supports. Finally, we introduce recent research and development (R&D) trends in the production of light hydrocarbons and middle distillates and in the catalytic processes being applied to the development of catalysts in Korea.
Keywords: Acidic site control; Active metal size; Catalyst design; Fischer; Hydrocarbons; Syngas; Tropsch